Blue light emitting ceramic nano-pigments of Tm3+ doped YAlO3: Applications in latent finger print, anti-counterfeiting and porcelain stoneware. (August 2016) - Darshan, G.P.; Premkumar, H.B.; Nagabhushana, H.; Sharma, S.C.; Prashantha, S.C.; Nagaswarup, H.P.; Prasad, B. Daruka
Abstract: A new class of ceramic pigments based on orthorhombic Thulium (Tm 3+ ) doped YAlO3 nanophosphors are synthesized by a simple and efficient low temperature solution combustion method using oxalyl dihydrazide (ODH) as fuel. The phosphors exhibit bright blue emission upon 359 nm excitation. Judd–Ofelt ( J–O ) theory is applied to a series of Tm 3+ doped phosphors based on their emission spectra. CIE chromaticity co-ordinates confirm blue emission of the phosphor. The prepared nano-phosphor was successful in developing latent fingerprint from various forensic relevant materials. A preliminary investigation of their anti-counterfeiting performance has been made, and the results indicate that the color emitting capability and high concealment makes this nanophosphor can provide a strengthened and more reliable anti-counterfeiting effect. As a result the optimized YAlO3 :Tm 3+ (3 mol%) phosphor is quite useful for potential application of pigments of desired color, solid state lighting, latent fingerprint, display and anti-counterfeiting applications. Graphical abstract: Highlights: First time quality of finger print was improved by using YAlO3 :Tm 3+ nanophosphor. CIE values of the samples were close to NTSC standard values of blue emission. Enhancement of fingermarks recognition was achieved by simple and quick method. YAlO3 :Tm 3+ nanophosphor showed applications in the anti-counterfeiting ink. Blue light emitting phosphor for future WLEDs and solid state lighting.